Analysis of Breastfeeding Patterns of Exclusive Breastfeeding for Mothers Carried Out Early Breastfeeding Initiation and the Factors that Influence it in the Working Area of the Ngantang Public Health Center - Husnul Khotimah; Sandu Siyoto; Siti Farida Noor Laili (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Early Breastfeeding Initiation a process of letting the baby's skin contact with the mother's skin for 1 hour, until the baby can suckle itself, Implementation of Early Breastfeeding Initiation, followed by exclusive breastfeeding, can reduce infant mortality, while the baby can grow more optimally and with quality. The low achievement of exclusive breastfeeding in Malang, especially in Puskesmas Ngantang, which is 49.1% is influenced by many factors. This study aims to analyze the influence, Early Breastfeeding Initiation, Husband Support, Mother's Live Status, and Mother's Motivation towards Exclusive Breastfeeding Breastfeeding Patterns, in the working area of ​​Ngantang Health Center in Malang Regency. This research uses quantitative analysis, using retrospective observation, and the Random sampling technique. Respondents were 151 nursing mothers whose babies were 6-12 months old. The location of the study was conducted in 13 villages in the Work Area of ​​the Ngantang Community Health Center, in February 2020. Results of the analysis of Early Breastfeeding Initiation (p = 0.352), Maternal Residence Status (p = 0.378), Husband Support (p = 0.872), had no significant effect about breastfeeding, only maternal motivation is influential (p = 0.026) Exclusive breastfeeding is indeed very difficult to do, many factors are needed for achieving exclusive breastfeeding, support from all parties is needed especially, great motivation from mothers to provide exclusive breastfeeding.